This Novel Approach New Blend Assistive Accessory - SARAVANAN, C.BALA; MOHAN, G. (IJRDO -Journal of Computer Science Engineering, 2016)
The Hybrid Assistive Limb (also known as HAL) is a powered exoskeleton suit or cyber-type strap-on robot suit developed by Japan’s Tsukuba University and the robotics company CYBERDYNE. It has been intended to sustain and expand the physical capabilities of its users, particularly people with physical disabilities. Professor Yoshiyuki Sankai’s robot suit, dubbed HAL™ for “Hybrid Assistive Limb”, is a major feat in science and technology, which enables elderly people to perform everyday tasks with which they would otherwise struggle, such as walking, climbing stairs or lifting heavy objects.